Predictive efficacy of chiropractic college assessment test scores in basic science chiropractic education. - Cunningham KA; DesJardins SL; Christensen MG (Journal of Manipulative & Physiological Therapeutics)
OBJECTIVE: To evaluate the ability of Chiropractic College Assessment Test (CCAT) to explain academic success within a chiropractic basic science curriculum. METHODS: The CCAT examination was administered to 202 subjects from 1 chiropractic college on the first day of classes. Zero-order Pearson correlations were used to examine for associations between the prechiropractic grade point average (GPA), CCAT scores, and basic science GPA. Multiple regression techniques were applied to determine the predictive efficacy of CCAT scores on basic science GPA. RESULTS: Study results indicate a correlation between prechiropractic GPA, CCAT scores (r = 0.348, P < .001), and basic science GPA (r = 0.559, P < .001). Correlation was also noted between CCAT scores and basic science GPA (r = 0.537, P < .001). Using multiple regression, together the variables (age, postsecondary education, prechiropractic GPA, and CCAT scores) accounted for a significant portion (R2 = 0.483, P < .001) of the total variance in basic science GPA. Furthermore, the CCAT scores accounted for significant unique explanation (change R2 = 0.081, P < .001) beyond that offered by the traditionally used prechiropractic GPA. CONCLUSION: The CCAT examination provides a valuable a priori indicator of success within the basic science curriculum of this particular chiropractic program. Consideration should be given to adopting the CCAT examination as one of a number of heuristic guides students and college officials use in making enrollment decisions.